Therapy with interferon-alpha plus ribavirin for membranoproliferative glomerulonephritis induced by hepatitis C virus - Lopes,Edmundo P.A. (2003)
We describe a treatment made with interferon-alpha (IFN-alpha) plus ribavirin of two patients with membranoproliferative glomerulonephritis (MPGN) induced by hepatitis C virus (HCV): Case 1 was a 22-year-old woman with leg and facial edema, hypertension and proteinuria, whose liver biopsy revealed chronic active hepatitis; and Case 2 was a 42-year-old man with anasarca, hypertension and proteinuria, whose liver biopsy indicated cirrhosis. Both had anti-HCV, HCV-RNA and cryoglobulins. IFN-alpha (3 million units (MU), 3 times/week) and ribavirin (1 g/day) were administered for 12 months. The drugs were well tolerated by both patients. Serum alanine aminotransferase (ALT) levels normalized and HCV-RNA became negative. Cryoglobulins disappeared and an improvement in renal disease was seen after 6 months of therapy. However, after 9 months, Case 2 presented ALT elevation, and proteinuria was detected. Two years after the end of therapy, both patients were negative in repeated HCV-RNA and cryoglobulin tests. Case 1 was asymptomatic, with normal liver and renal tests, and Case 2 had normal blood pressure, with mild edema of the ankles. Based on the evolution of these two cases, the association of IFN-alpha and ribavirin may be a therapeutic option for patients with MPGN related to HCV.